Ethylene-vinyl alcohol copolymer and method for producing the same

By introducing molecules with specific terminal structures into EVOH and adding metal ions and carboxylic acids to the resin composition, the problem of poor viscosity stability in the early stage of melting in the prior art is solved, and the stable melt forming process and color resistance under high-temperature alkaline conditions are achieved.

CN113924322BActive Publication Date: 2025-04-01KURARAY CO LTD

Patent Information

Application Number
CN201980097525.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2019-04-15
Publication Date
2025-04-01
Estimated Expiration
2039-04-15

AI Technical Summary

Technical Problem

The existing resin composition containing EVOH is insufficient in viscosity at the beginning of melting, resulting in unstable melt forming process, deviation of the performance of the molded body, and easy coloring under high temperature and alkaline conditions.

Method used

By introducing molecules of a specific terminal structure into EVOH, specifically, molecules containing structure (I) and structure (II) at the terminal, and adding metal ions and carboxylic acids to the resin composition to improve viscosity stability and color resistance at the beginning of melting.

Benefits of technology

Excellent viscosity stability at the beginning of melting, stable melt forming process, and excellent color resistance under high temperature and alkaline conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113924322B_ABST
    Figure CN113924322B_ABST
Patent Text Reader

Abstract

Ethylene-vinyl alcohol copolymer, wherein the ethylene unit content is 15 to 60 mol% and the saponification degree is 85 mol% or more. The aforementioned copolymer contains molecules having the following structure (I) at the terminals and molecules having structure (II) at the terminals. The total content of structure (I) and structure (II) is 0.002 to 0.020 mol% based on the total amount of all monomer units, and the molar ratio R[I / (I+II)] of structure (I) to the total of structure (I) and structure (II) satisfies the following formula (1). This ethylene-vinyl alcohol copolymer has excellent viscosity stability at the initial stage of melting start, can stabilize the melt forming process, and also has excellent color resistance under high temperature (e.g., 80 °C) and alkaline conditions. [In formula (I), Y is a hydrogen atom or a methyl group.][In formula (II), Z is a hydrogen atom or a methyl group.] 0.8 < R + Et / 100 (1) [In formula (1), Et is the aforementioned ethylene unit content (mol%).].
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an ethylene-vinyl alcohol copolymer, a resin composition and a molded article containing the same, and a method for producing the same. Background Art

[0002] Ethylene-vinyl alcohol copolymer (hereinafter sometimes abbreviated as "EVOH") has excellent gas barrier properties and melt formability. Therefore, it is formed into films, sheets, pipes, tubes, bottles, etc. by various melt forming methods, and is widely used as packaging materials in the food field and industrial field that require gas barrier properties. In order to stably manufacture packaging materials with uniform performance and quality such as gas barrier properties, mechanical properties, and appearance, it is preferred that the melt viscosity of EVOH change over time is small. However, EVOH having multiple active reactive groups at the molecular ends and in the molecular chains will competitively undergo multiple cross-linking reactions and decomposition reactions, so the time-varying behavior of the melt viscosity is complicated. Due to this time-varying change in melt viscosity, sometimes the resin pressure, resin temperature, and thickness distribution of the molded body during melt forming also change, causing problems in the melt forming process and the performance of the resulting molded body.

[0003] In order to improve the long-term stability of the melt viscosity of EVOH (hereinafter sometimes abbreviated as "long-term operability") and stably produce packaging materials with uniform performance / quality, various resin compositions containing EVOH have been proposed. For example, Patent Document 1 records a resin composition containing EVOH, a boron compound, sodium acetate and magnesium acetate. And it is recorded that: According to this resin composition, the long-term operability during melt molding can be improved. Patent Document 2 records a resin composition containing EVOH and a conjugated polyene compound. And it is recorded that: According to this resin composition, the generation of gel and particles due to melt molding can be suppressed. Patent Document 3 records a resin composition containing EVOH, a specific carboxylic acid metal salt and a hindered phenol-based antioxidant. And it is recorded that: The resin composition has excellent thermal stability and suppresses the formation of oxidative gel at high temperatures. Patent Document 4 records a resin composition containing EVOH and a specific unsaturated aldehyde. And it is recorded that: According to this resin composition, defects such as fish eyes and gels due to melt molding can be suppressed, and the long-term operability during melt molding can be improved.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 11-60874

[0007] Patent Document 2: Japanese Patent Application Laid-Open No. 9-71620

[0008] Patent Document 3: Japanese Patent Application Laid-Open No. 4-227744

[0009] Patent document 4: International Publication No. 2013 / 146961. Summary of the invention

[0010] Problems to be solved by the invention

[0011] It is clear that the above-mentioned resin composition containing EVOH has a certain effect on inhibiting the resin that has been retained in the extruder for a long time from forming gels and controlling the melt viscosity, but the viscosity stability at the beginning of melting is insufficient. Therefore, sometimes the resin temperature and pressure are not fixed, the resin ejection amount during melt molding is uneven, the melt molding process is still unstable, and various properties such as gas barrier properties and mechanical properties of the obtained molded body are deviated. In addition, coloring sometimes occurs under high temperature (e.g. 80°C) and alkaline conditions. Therefore, the purpose of the present invention is to provide EVOH that has excellent viscosity stability at the beginning of melting, can stabilize the melt molding process, and has excellent coloring resistance under high temperature (e.g. 80°C) and alkaline conditions.

[0012] Methods used to solve problems

[0013] As a result of in-depth research, the present inventors found that when a conventional resin composition containing EVOH is melt-molded, the following phenomenon is widely observed: a sharp increase in viscosity occurs at the beginning of melting (5 to 20 minutes after the beginning of melting), and then the viscosity slowly decreases for tens of minutes before increasing again. This complex viscosity change causes the instability of the melt molding process. In addition, it was found that this viscosity behavior, especially the sharp increase in viscosity at the beginning of melting, is significantly related to the terminal structure of the molecules constituting EVOH derived from the polymerization initiator. In addition, the EVOH of the present invention containing molecules having a specific terminal structure was completed.

[0014] That is, the present invention is as follows.

[0015] [1] EVOH, wherein the ethylene unit content is 15 to 60 mol % and the saponification degree is 85 mol % or more, the copolymer comprises a molecule having the following structure (I) at the terminal and a molecule having the following structure (II) at the terminal, the total content of the structure (I) and the structure (II) is 0.002 to 0.020 mol % relative to all monomer units, and the molar ratio R [I / (I+II)] of the structure (I) to the total of the structure (I) and the structure (II) satisfies the following formula (1);

[0016] [Chemistry 1]

[0017]

[0018] [In formula (I), Y is a hydrogen atom or a methyl group.]

[0019] [Chemistry 2]

[0020]

[0021] [In formula (II), Z is a hydrogen atom or a methyl group.]

[0022] 0.8 <R+Et / 100 (1)

[0023] [In formula (1), Et is the aforementioned ethylene unit content (mol %).]

[0024] [2] The EVOH according to [1], which satisfies the following formula (2);

[0025] 0.9 <R+Et / 100 (2)

[0026] [In formula (2), R and Et are the same as in formula (1).]

[0027] [3] A resin composition comprising the EVOH of [1] or [2] and 100 to 400 ppm of a metal ion;

[0028] [4] The resin composition according to [3], which contains 50 to 400 ppm of carboxylic acid;

[0029] [5] A shaped article comprising the EVOH of [1] or [2];

[0030] [6] A molded article comprising the resin composition of [3] or [4];

[0031] [7] The method for producing EVOH according to [1] or [2] comprises the following steps: a copolymerization step of copolymerizing ethylene and vinyl ester in a solution using an alkoxy group-containing azonitrile compound as a polymerization initiator to obtain an ethylene-vinyl ester copolymer solution; and a saponification step of saponifying the ethylene-vinyl ester copolymer in the solution in the presence of an alkali catalyst to obtain EVOH, wherein in the saponification step, 1.2 mol or more of the alkali catalyst is used relative to 1 mol of the vinyl ester component contained in the ethylene-vinyl ester copolymer, and the solution is irradiated with ultrasonic waves or microwaves.

[0032] Effects of the Invention

[0033] The EVOH of the present invention is excellent in viscosity stability at the initial stage of melting, can stabilize the melt molding process, and is also excellent in coloration resistance under high temperature (eg 80° C.) and alkaline conditions. DETAILED DESCRIPTION

[0034] <Ethylene-vinyl alcohol copolymer>

[0035] The EVOH of the present invention has an ethylene unit content of 15 to 60 mol% and a saponification degree of 85 mol% or more. The copolymer comprises a molecule having the following structure (I) at the terminal and a molecule having the structure (II) at the terminal. The total content of the structure (I) and the structure (II) is 0.002 to 0.020 mol% relative to all monomer units, and the molar ratio R [I / (I+II)] of the structure (I) to the total of the structure (I) and the structure (II) satisfies the following formula (1).

[0036] [Chemistry 1]

[0037]

[0038] [In formula (I), Y is a hydrogen atom or a methyl group.]

[0039] [Chemistry 2]

[0040]

[0041] [In formula (II), Z is a hydrogen atom or a methyl group.]

[0042] 0.8 <R+Et / 100 (1)

[0043] [In formula (1), Et is the aforementioned ethylene unit content (mol %). ]

[0044] The EVOH of the present invention has ethylene units and vinyl alcohol units as main structural units. In addition, the aforementioned EVOH contains vinyl ester units as optional components. And, the EVOH of the present invention contains molecules containing structure (I) at the end and molecules containing structure (II) at the end. The total content of structure (I) and structure (II) in the aforementioned EVOH is 0.002~0.020 mol% relative to all monomer units. As a result, the viscosity stability of the aforementioned EVOH at the beginning of melting is improved. On the other hand, when the aforementioned total content is greater than 0.020 mol%, the resulting molded body sometimes undergoes coloring under alkaline conditions or produces appearance abnormalities such as foaming during melt molding at high temperatures. The aforementioned total content is preferably less than 0.012 mol%. On the other hand, in order to make the aforementioned total content less than 0.002 mol%, it is necessary to extremely reduce the polymerization rate, which is not realistic from an economic point of view. It should be noted that in this specification, the monomer units in the ethylene-vinyl alcohol copolymer refer to ethylene units, vinyl alcohol units, vinyl ester units, and other monomer units copolymerized as needed, and all monomer units refer to the total amount of the number of moles of each monomer unit. In this case, the unit including the terminal structure represented by the structure (I) or the structure (II) is also included in the monomer unit and calculated.

[0045] In the EVOH of the present invention, the molar ratio R [I / (I+II)] of the structure (I) to the total of the structure (I) and the structure (II) must satisfy the following formula (1), and preferably satisfies the following formula (2).

[0046] 0.8 <R+Et / 100 (1)

[0047] 0.9 <R+Et / 100 (2)

[0048] [In formula (1) and formula (2), Et is the aforementioned ethylene unit content (mol %). ]

[0049] Here, the right sides of formula (1) and formula (2) are both the sum of the molar ratio R [I / (I+II)] of structure (I) in the aforementioned EVOH to the sum of structure (I) and structure (II) plus the molar ratio of the ethylene unit in the aforementioned EVOH to all monomer units (ethylene unit / total monomer units).

[0050] Formula (1) and formula (2) indicate that the sum must be greater than a certain value, and when Et is small, the molar ratio R must be a large value. As described later, both structure (I) and structure (II) are structures derived from the polymerization initiator used in the polymerization process. Among them, structure (I) contains a cyclic ester structure formed by the reaction of a nitrile group derived from a polymerization initiator with a hydroxyl group in the same molecule, and structure (II) is the structure before such reaction occurs. Therefore, the large value on the right side of formula (1) and formula (2) means that the proportion of products obtained by converting the nitrile group derived from the polymerization initiator into the above-mentioned cyclic ester structure is high, and formula (2) means that the proportion is higher. By satisfying formula (1), the viscosity stability of the EVOH of the present invention at the beginning of melting is improved, and therefore, the rapid viscosity increase at the beginning of melting (5 to 20 minutes after the beginning of melting) can be suppressed. If formula (2) is satisfied, such viscosity increase is further suppressed.

[0051] The reason for showing such characteristics is still uncertain, but the following reasons can be speculated. It can be speculated that if structure (II) is present, a cross-linking reaction between molecules is likely to occur in a molten state. On the other hand, it can be considered that structure (I) is a structure in which cyclization has already occurred within the same molecule, so this cross-linking reaction is difficult to occur even if structure (I) is present. It can be speculated that this can suppress the increase in viscosity at the beginning of melting. The content and molar ratio R [I / (I+II)] of structure (I) and structure (II) can be determined by nuclear magnetic resonance (NMR) method.

[0052] From the viewpoint of further improving the viscosity stability at the initial stage of melting, in the EVOH of the present invention, the molar ratio R [I / (I+II)] of structure (I) to the total of structure (I) and structure (II) is preferably 0.5 or more, more preferably 0.6 or more. On the other hand, the molar ratio R [I / (I+II)] is preferably 0.99 or less.

[0053] The ethylene unit content of EVOH of the present invention (i.e., the ratio of the molar number of ethylene units in EVOH to the total molar number of all monomer units) is in the range of 15 to 60 mol%. The lower limit of the ethylene unit content of EVOH is preferably 20 mol%, more preferably 23 mol%. On the other hand, the upper limit of the ethylene unit content of EVOH is preferably 55 mol%, more preferably 50 mol%. If the ethylene unit content of EVOH is less than 15 mol%, the gas barrier properties under high humidity are sometimes reduced, and the melt formability is also deteriorated. On the contrary, if the ethylene unit content of EVOH exceeds 60 mol%, sufficient gas barrier properties are sometimes not obtained. The ethylene unit content and saponification degree of EVOH can be obtained by nuclear magnetic resonance (NMR) method.

[0054] The saponification degree of EVOH (i.e., the ratio of the molar number of vinyl alcohol units in EVOH to the total molar number of vinyl alcohol units and vinyl ester units) is 85 mol% or more. The lower limit of the saponification degree of EVOH is preferably 95 mol%, more preferably 99 mol%. On the other hand, the upper limit of the saponification degree of EVOH is preferably 100 mol%, more preferably 99.99 mol%. If the saponification degree of EVOH is less than 85 mol%, sufficient gas barrier properties may not be obtained, and further, thermal stability may also be insufficient.

[0055] The melt flow rate (temperature 210° C., load 2160 g; hereinafter sometimes abbreviated as “MFR”) of EVOH based on JIS K 7210:2014 is generally 0.1 g / 10 min in lower limit and 50 g / 10 min in upper limit.

[0056] EVOH may contain monomer units other than ethylene units, vinyl alcohol units, and vinyl ester units as copolymer units within a range that does not impair the effects of the present invention. Examples of monomers include α-olefins such as propylene, 1-butene, isobutylene, 4-methyl-1-pentene, 1-hexene, and 1-octene; unsaturated carboxylic acids such as itaconic acid, methacrylic acid, acrylic acid, and maleic acid, their salts, partial esters or full esters, nitriles, amides, and anhydrides; vinyl silane compounds such as vinyl trimethoxysilane, vinyl triethoxysilane, vinyl tri(β-methoxyethoxy)silane, and γ-methacryloxypropyl trimethoxysilane; unsaturated sulfonic acids or their salts; unsaturated thiols; and vinyl pyrrolidones. The content of monomer units other than ethylene units, vinyl alcohol units, and vinyl ester units in EVOH is generally 5 mol% or less, preferably 2 mol% or less, and more preferably 1 mol% or less.

[0057] The resin composition containing the above-mentioned EVOH is a suitable embodiment of the present invention. The content of EVOH in the resin composition is usually 70% by mass or more, preferably 80% by mass or more, and more preferably 90% by mass or more. If the content of EVOH is set to this range, the melt moldability of the resin composition of the present invention is improved, and the gas barrier property and oil resistance of the obtained molded body are also excellent. Regarding the resin composition of the present invention, the resin contained in the resin composition can be substantially composed of only EVOH, or it can be composed of only EVOH.

[0058] <Metal ions>

[0059] The resin composition of the present invention preferably also contains metal ions. If the resin composition of the present invention contains metal ions, the interlayer adhesion when made into a multilayer molded body, i.e., a multilayer structure, is excellent. The reason for the improvement of interlayer adhesion is still uncertain, but it can be considered that when a molecule having a functional group that can react with the hydroxyl group of EVOH is contained in a layer adjacent to the layer containing the aforementioned resin composition, the bonding reaction between the two is accelerated by the metal ions. In addition, if the ratio of the metal ions to the carboxylic acid described later is controlled, the melt formability and coloring resistance of the resin composition of the present invention can also be improved.

[0060] When the resin composition of the present invention contains metal ions, the lower limit of the content is preferably 100ppm, more preferably 150ppm. On the other hand, the upper limit of the content of the metal ions is preferably 400ppm, more preferably 350ppm. If the content of the metal ions is less than 100ppm, the interlayer adhesion of the obtained multilayer structure is sometimes insufficient. On the other hand, if the content of the metal ions is greater than 400ppm, the coloring resistance is sometimes insufficient.

[0061] As metal ions, alkali metal ions, alkaline earth metal ions, and other transition metal ions can be listed, and they can include one or more. Among them, alkali metal ions are preferred. From the viewpoint of being able to easily manufacture the aforementioned resin composition and the viewpoint of being able to further improve the interlayer adhesion of the multilayer structure, it is preferred that the metal ions consist only of alkali metal ions.

[0062] As the alkali metal ion, for example, ions of lithium, sodium, potassium, rubidium, and cesium can be listed. From the viewpoint of ease of industrial acquisition, ions of sodium or potassium are preferred. In addition, as alkali metal salts that provide alkali metal ions, for example, aliphatic carboxylates, aromatic carboxylates, carbonates, hydrochlorides, nitrates, sulfates, phosphates, and metal complexes can be listed. Among them, from the viewpoint of easy acquisition, sodium acetate, potassium acetate, sodium phosphate, and potassium phosphate are more preferred.

[0063] As metal ions, sometimes it is also preferred to include alkaline earth metal ions. If the metal ions include alkaline earth metal ions, for example, the thermal degradation of EVOH when recycling scraps and reusing can be suppressed sometimes, and the resulting molded body can be suppressed to produce gel and particles. As alkaline earth metal ions, for example, ions of beryllium, magnesium, calcium, strontium, and barium can be listed, and from the viewpoint of industrial ease of acquisition, it is preferably an ion of magnesium or calcium. In addition, as alkaline earth metal salts providing alkaline earth metal ions, for example, aliphatic carboxylates, aromatic carboxylates, carbonates, hydrochlorides, nitrates, sulfates, phosphates, and metal complexes can be listed.

[0064] <Carboxylic Acid>

[0065] The resin composition of the present invention preferably further contains a carboxylic acid. If the resin composition of the present invention contains a carboxylic acid, the melt moldability and color resistance at high temperature of the resin composition of the present invention can be improved. In particular, from the viewpoint of improving the pH buffering capacity of the obtained resin composition and sometimes improving the color resistance to acidic substances and alkaline substances, the pKa of the carboxylic acid is more preferably in the range of 3.5 to 5.5.

[0066] When the resin composition of the present invention contains carboxylic acid, the lower limit of its content is preferably 50ppm, more preferably 100ppm. On the other hand, the upper limit of the content of carboxylic acid is preferably 400ppm, more preferably 350ppm. If the content of carboxylic acid is less than 50ppm, the coloring resistance is sometimes insufficient due to high temperature. On the other hand, if the content of carboxylic acid is greater than 400ppm, the melt formability is sometimes insufficient or the odor becomes a problem. The carboxylic acid content in the resin composition is calculated by titrating the extract obtained by extracting 10g of the resin composition with 50ml of pure water at 95°C for 8 hours. Here, as the carboxylic acid content in the resin composition, the content of the carboxylate present in the above-mentioned extract is not considered.

[0067] As carboxylic acid, monocarboxylic acid and polycarboxylic acid can be listed, and they can include 1 or more. When including monocarboxylic acid and polycarboxylic acid as carboxylic acid, sometimes the melt formability of obtained resin composition, the color resistance under high temperature can be further improved. In addition, polycarboxylic acid can have more than 3 carboxyl groups. In this case, sometimes the color resistance of resin composition of the present invention can be further improved.

[0068] Monocarboxylic acid refers to a compound having one carboxyl group in the molecule. Preferably, the pKa of the monocarboxylic acid is in the range of 3.5 to 5.5. Examples of such monocarboxylic acids include formic acid (pKa = 3.77), acetic acid (pKa = 4.76), propionic acid (pKa = 4.85), butyric acid (pKa = 4.82), caproic acid (pKa = 4.88), capric acid (pKa = 4.90), lactic acid (pKa = 3.86), acrylic acid (pKa = 4.25), methacrylic acid (pKa = 4.65), benzoic acid (pKa = 4.20), and 2-naphthoic acid (pKa = 4.17). As long as the pKa of these carboxylic acids is in the range of 3.5 to 5.5, they may have substituents such as hydroxyl groups, amino groups, and halogen atoms. Among them, acetic acid is preferred from the perspective of high safety and easy handling.

[0069] Polycarboxylic acid refers to a compound having two or more carboxyl groups in the molecule. In this case, it is preferred that the pKa of at least one carboxyl group is in the range of 3.5 to 5.5. Examples of such polycarboxylic acids include oxalic acid (pKa2=4.27), succinic acid (pKa1=4.20), fumaric acid (pKa2=4.44), malic acid (pKa2=5.13), glutaric acid (pKa1=4.30, pKa2=5.40), adipic acid (pKa1=4.43, pKa2=5.41), pimelic acid (pKa1=4.71), phthalic acid (pKa2=5.41), isophthalic acid (pKa2=4.46), terephthalic acid (pKa1=3.51, pKa2=4.82), citric acid (pKa2=4.75), tartaric acid (pKa2=4.40), glutamic acid (pKa2=4.07), and aspartic acid (pKa=3.90).

[0070] <Other ingredients>

[0071] The resin composition of the present invention may further contain other components within the range that does not impair the effects of the present invention. Examples of other components include phosphoric acid compounds, boron compounds, thermoplastic resins other than EVOH, crosslinking agents, desiccants, oxidation accelerators, antioxidants, oxygen absorbers, plasticizers, lubricants, heat stabilizers (melt stabilizers), processing aids, surfactants, deodorants, antistatic agents, ultraviolet absorbers, antifogging agents, flame retardants, pigments, dyes, fillers, fillers, various fibers and other reinforcing agents.

[0072] When the resin composition of the present invention contains a phosphoric acid compound, the lower limit of its content is usually calculated as 1ppm according to the phosphate conversion. On the other hand, the upper limit of the above-mentioned content is usually calculated as 200ppm according to the phosphate conversion. If the phosphoric acid compound is contained in this range, the thermal stability of the resin composition of the present invention can sometimes be improved. In particular, the generation and coloring of gel-like particles during melt molding for a long time can sometimes be suppressed. As the phosphoric acid compound, various acids such as phosphoric acid and phosphorous acid, their salts, etc. can be used. Phosphate can be any form of dihydrogen phosphate, monohydrogen phosphate, and phosphate. As cationic species of phosphate, alkali metals and alkaline earth metals can be listed. As the phosphoric acid compound, specifically, phosphoric acid compounds in the form of sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate, and dipotassium hydrogen phosphate can be listed.

[0073] When the resin composition of the present invention contains a boron compound, the lower limit of its content is usually calculated as 5ppm according to the conversion of the boron element. On the other hand, the upper limit of the content is usually calculated as 1000ppm according to the conversion of the boron element. If the boron compound is contained in this range, the thermal stability during the melt molding of the resin composition of the present invention can be improved sometimes, and the generation of gel-like particles can be suppressed. In addition, the mechanical properties of the resulting molded body can also be improved sometimes. It can be inferred that the reason for these effects is that a chelating interaction occurs between EVOH and the boron compound. As a boron compound, for example, boric acid, boric esters, borates, and boron hydrides can be listed. Specifically, as boric acid, for example, orthoboric acid (H3BO3), metaboric acid, and tetraboric acid can be listed, as boric esters, for example, trimethyl borate and triethyl borate can be listed, and as borates, for example, alkali metal salts, alkaline earth metal salts, and borax of the aforementioned boric acids can be listed.

[0074] Examples of thermoplastic resins other than EVOH include various polyolefins (polyethylene, polypropylene, poly-1-butene, poly-4-methyl-1-pentene, ethylene-propylene copolymers, copolymers of ethylene and α-olefins having 4 or more carbon atoms, copolymers of polyolefins and maleic anhydride, ethylene-vinyl ester copolymers, ethylene-acrylate copolymers, or modified polyolefins obtained by grafting these with unsaturated carboxylic acids or derivatives thereof), various polyamides (nylon 6, nylon 6 / 6, nylon 6 / 66 copolymers, nylon 11, nylon 12, poly(m-xylylene adipamide), various polyesters (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate), polyvinyl chloride, polyvinylidene chloride, polystyrene, polyacrylonitrile, polyurethane, polycarbonate, polyacetal, polyacrylate, and modified polyvinyl alcohol resins. The content of the thermoplastic resin in the resin composition is usually less than 30% by mass, preferably less than 20% by mass, and more preferably less than 10% by mass.

[0075] <molded body>

[0076] A molded body comprising the EVOH of the present invention is a suitable embodiment of the present invention. In this case, it is more suitable to use the aforementioned resin composition as the aforementioned EVOH. The aforementioned EVOH can be made into a molded body of a single-layer structure, or it can be made into a molded body of a multilayer structure of two or more together with various other substrates, that is, a multilayer structure. As molding methods, for example, extrusion molding, thermoforming, irregular shape molding, hollow molding, rotational molding, and injection molding can be listed. The uses of the molded body of the present invention are various, and for example, films, sheets, containers, bottles, cans, catheters, hoses, etc. can be listed.

[0077] As specific forming methods, for example, films, sheets, tubes, and hoses can be formed by extrusion molding, container shapes can be formed by injection molding, and hollow containers such as bottles and cans can be formed by hollow molding and rotational molding. Examples of hollow molding include: extrusion hollow molding in which a preform is formed by extrusion molding and air is blown thereto; and injection hollow molding in which a preformed foam is formed by injection molding and air is blown thereto. In the manufacture of flexible packaging materials and containers, a method of forming a packaging material such as a multilayer film by extrusion molding can be appropriately used; and a method of thermoforming a multilayer sheet formed by extrusion molding to form a container-shaped packaging material.

[0078] <Multilayer structure>

[0079] The above-mentioned molded body is preferably a multilayer structure containing a layer comprising a resin composition of the present invention. The multilayer structure is obtained by laminating a layer comprising a resin composition of the present invention with other layers. As the layer composition of the multilayer structure, if the layer comprising the resin except the resin composition of the present invention is recorded as the x layer, the resin composition layer of the present invention is recorded as the y layer, and the adhesive resin layer is recorded as the z layer, then for example x / y, x / y / x, x / z / y, x / z / y / z / x, x / y / x / y / x, x / z / y / z / x / z / y / z / x, etc. can be listed. When multiple x layers, y layers, and z layers are set, their types can be the same or different. In addition, the layer obtained by using the recycled resin containing the waste materials such as the scraps generated during molding can be separately provided, and the recycled resin can also be mixed into the layer comprising other resins. Regarding the thickness composition of each layer of the multilayer structure, from the viewpoints of formability and cost, the thickness of the y layer is usually 2~20% relative to the ratio of the thickness of all layers.

[0080] The resin used in the aforementioned x layer is preferably a thermoplastic resin from the viewpoint of processability, etc. Examples of the thermoplastic resin include various polyolefins (polyethylene, polypropylene, poly-1-butene, poly-4-methyl-1-pentene, ethylene-propylene copolymers, copolymers of ethylene and α-olefins having 4 or more carbon atoms, copolymers of polyolefins and maleic anhydride, ethylene-vinyl ester copolymers, ethylene-acrylate copolymers, or modified polyolefins obtained by grafting them with unsaturated carboxylic acids or their derivatives, etc.), various polyamides (nylon 6, nylon 6 / 6, nylon 6 / 66 copolymers, nylon 11, nylon 12, poly(m-xylene adipamide), etc.), various polyesters (polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), polyvinyl chloride, polyvinylidene chloride, polystyrene, polyacrylonitrile, polyurethane, polycarbonate, polyacetal, polyacrylate, and modified polyvinyl alcohol resin. The thermoplastic resin layer may be unstretched, or may be stretched or calendered along a single axis or a double axis. Among them, polyolefins are preferred from the viewpoints of moisture resistance, mechanical properties, economy, and heat sealability, and polyamides and polyesters are preferred from the viewpoints of mechanical properties and heat resistance.

[0081] On the other hand, the adhesive resin used in the z layer can be any adhesive resin as long as it can bond the layers together. For example, a polyurethane or polyester one-component or two-component curable adhesive, or a carboxylic acid-modified polyolefin is suitable. Here, the carboxylic acid-modified polyolefin refers to a polyolefin copolymer containing an unsaturated carboxylic acid or its anhydride (maleic anhydride, etc.) as a copolymer component, or a graft copolymer obtained by grafting an unsaturated carboxylic acid or its anhydride onto a polyolefin.

[0082] As a method for obtaining a multilayer structure, for example, coextrusion molding, coextrusion blow molding, co-injection molding, extrusion lamination, coextrusion lamination, dry lamination, solution coating, etc. can be cited. It should be noted that for the multilayer structure obtained by this method, it is possible to further perform secondary processing and molding by methods such as vacuum pressure deep drawing molding, blow molding, and pressure molding after reheating in the range below the melting point of EVOH, thereby forming the target molded body structure. In addition, it is also possible to perform uniaxial or biaxial stretching on the multilayer structure after reheating in the range below the melting point of EVOH by methods such as roll stretching method, pantograph stretching method, and inflation stretching method, thereby obtaining a stretched multilayer structure.

[0083] <Manufacturing method of EVOH>

[0084] The manufacturing method of EVOH of the present invention includes: (i) a copolymerization step of copolymerizing ethylene and vinyl ester to obtain an ethylene-vinyl ester copolymer; and, (ii) a saponification step of saponifying the aforementioned ethylene-vinyl ester copolymer in the presence of a base catalyst to obtain an ethylene-vinyl alcohol copolymer. In particular, from the viewpoint of easily manufacturing the aforementioned EVOH, the following manufacturing method of EVOH is extremely preferred, which includes the following steps: a copolymerization step of copolymerizing ethylene and vinyl ester in a solution using an azo nitrile compound containing an alkoxy group as a polymerization initiator to obtain an ethylene-vinyl ester copolymer solution; and, a saponification step of saponifying the ethylene-vinyl ester copolymer in the aforementioned solution in the presence of a base catalyst to obtain an ethylene-vinyl alcohol copolymer. In the aforementioned saponification step, with respect to 1 mole of the vinyl ester component contained in the ethylene-vinyl ester copolymer, 1.2 moles or more of the base catalyst is used, and ultrasonic waves or microwaves are irradiated to the aforementioned solution.

[0085] When manufacturing the EVOH of the present invention, it is preferably based on (i) a copolymerization step of copolymerizing ethylene and vinyl ester to obtain an ethylene-vinyl ester copolymer, and (ii) a saponification step of saponifying the ethylene-vinyl ester copolymer in the presence of a base catalyst, and further includes the following steps: (iii) a granulation step of obtaining a water-containing granule by a granulation operation, and (iv) a drying step of drying the water-containing granule to obtain EVOH. Hereinafter, each step will be described.

[0086] <(i) Copolymerization step>

[0087] The copolymerization process includes, on the basis of the process of copolymerizing ethylene and vinyl ester, further comprising: adding a polymerization inhibitor as needed, and then removing unreacted ethylene and unreacted vinyl ester to obtain an ethylene-vinyl ester copolymer solution. As the copolymerization method of ethylene and vinyl ester, known methods such as solution polymerization, suspension polymerization, emulsion polymerization, and bulk polymerization can be listed, and solution polymerization methods are suitable. As the vinyl ester, aliphatic vinyl esters such as vinyl acetate, vinyl propionate, and vinyl pivalate are preferred, and vinyl acetate is more preferred. It should be noted that other monomers that can be copolymerized with ethylene and vinyl ester can be copolymerized in small amounts within the range that does not impair the effect of the present invention. The polymerization temperature is preferably 20~90°C, more preferably 40~70°C. The polymerization time is generally 2~15 hours. The polymerization rate is preferably 10~90% relative to the vinyl ester fed, and more preferably 30~80%. The resin content in the reaction solution after polymerization is generally 5~85% by mass.

[0088] In the copolymerization process, an azonitrile compound containing an alkoxy group is used as a polymerization initiator. As an azonitrile compound containing an alkoxy group suitable for use in the present invention, for example, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(4-ethoxy-2,4-dimethylvaleronitrile), etc. can be cited, among which 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) is preferred. These azonitrile compounds containing alkoxy groups are not prone to abnormal decomposition caused by contact with metals, and also have a high decomposition rate at low temperatures. Therefore, by using the aforementioned azonitrile compounds, ethylene and vinyl ester can be copolymerized safely, effectively and economically. Specifically, in the aforementioned copolymerization process, it is preferred that an azonitrile compound containing an alkoxy group is used as a polymerization initiator, and ethylene and vinyl ester are copolymerized in a solution to obtain an ethylene-vinyl ester copolymer solution.

[0089] <(ii) Saponification step>

[0090] Next, by adding an alkali catalyst to the ethylene-vinyl ester copolymer solution, the ethylene-vinyl ester copolymer in the solution is saponified to obtain an ethylene-vinyl alcohol copolymer. The saponification process can be carried out in any manner of a continuous method or an intermittent method. Examples of the alkali catalyst include sodium hydroxide, potassium hydroxide, and alkali metal alcohol salts. In order to control the molar ratio R[I / (I+II)] in a manner that satisfies formula (1), it is extremely preferred in the saponification process that: 1.2 moles or more of the alkali catalyst is used relative to 1 mole of the vinyl ester component contained in the ethylene-vinyl ester copolymer, and the solution is irradiated with ultrasound or microwaves.

[0091] Here, relative to 1 mol of vinyl ester component, it is more preferred to use 2 mol or more of the alkali catalyst. During the saponification reaction, as long as the aforementioned ethylene-vinyl ester copolymer solution (reaction solution) to which the alkali catalyst is added can be irradiated with one or more of ultrasound and microwave, there is no particular limitation on the irradiation method, the irradiation device used, and the irradiation site. The wavelength and intensity of the ultrasound or microwave to be irradiated are also not particularly limited. The irradiation time is also not particularly limited, as long as the ultrasound or microwave is irradiated for at least a portion of the time in the saponification reaction. For example, as described in detail in the embodiments, the following method can be used: using an ultrasonic cleaner (US CLEANER USK-2R), with an output power of 80W and a frequency of 40kHz, the reaction solution of the last 15 to 60 minutes of the saponification reaction is irradiated with ultrasound; after the aforementioned ethylene-vinyl ester copolymer solution (reaction solution) to which the alkali catalyst is added is heated, a microwave irradiation device (made by Anton Paar, Multiwave3000 type) is used, the output power is set to 800W, and the aforementioned reaction solution is irradiated with microwaves for 2 hours at a frequency of 2450MHz (2.45GHz), etc. In addition, after the saponification step, an operation of neutralizing the remaining alkali catalyst by adding an acid such as acetic acid is generally performed.

[0092] <(iii) Granulation process>

[0093] The granulation step can be performed by, for example, the following methods: (1) a method of extruding the reaction liquid obtained by the saponification step into a low-temperature poor solvent to precipitate or solidify the copolymer, followed by cutting immediately or further cooling and solidifying and then cutting to obtain water-containing pellets; (2) a method of contacting the reaction liquid obtained by the saponification step with water vapor to prepare a water-containing resin composition in advance, and then cutting to obtain water-containing pellets; (3) a method of adding water to the reaction liquid obtained by the saponification step to precipitate the copolymer, and then pulverizing the copolymer to obtain water-containing pellets. The water content of the water-containing pellets is generally 50 to 200 parts by mass relative to 100 parts by mass of EVOH.

[0094] <(iv) Drying process>

[0095] It is preferred to subject the water-containing pellets obtained in the granulation step to a drying step to produce dry pellets of EVOH. For the purpose of preventing the formation of voids during the forming process, the water content in the dry pellets is preferably 1.0 mass part or less, more preferably 0.5 mass part or less, and further preferably 0.3 mass part or less relative to 100 mass parts of EVOH. As drying methods, for example, static drying and fluidized drying can be listed, and they can be used alone or in combination. The drying step can be carried out by any method of continuous or intermittent. When a plurality of drying methods are combined, the continuous or intermittent method can be freely selected for each drying method. It should be noted that if the drying step is carried out in a low oxygen concentration or in an anaerobic state, it is preferred from the point of view of being able to reduce the deterioration of EVOH caused by oxygen during drying.

[0096] The contents of structure (I) and structure (II) can be controlled by adjusting the amount of polymerization initiator used, the temperature and time until the addition of the polymerization initiator, the polymerization temperature, the polymerization time, the polymerization rate, the type and amount of the polymerization solvent in the copolymerization step, adjusting the amount of the alkali catalyst in the saponification step, or irradiating with ultrasonic waves or microwaves. In addition, the contents of structure (I) and structure (II) may change in the granulation step or the drying step.

[0097] It should be noted that as a method for producing a resin composition by making the EVOH of the present invention contain various components such as metal ions and carboxylic acids, for example, a method of mixing the above-mentioned pellets with the various components and melt-kneading them; a method of mixing the various components when preparing the above-mentioned pellets; a method of immersing the above-mentioned pellets in a solution containing the various components, etc. As the pellets, both water-containing pellets and dry pellets can be used.

[0098] The EVOH of the present invention thus obtained is excellent in viscosity stability at the initial stage of melting, and therefore, molded products such as pellets, films, sheets, and containers can be stably produced. Example

[0099] Hereinafter, the present invention will be specifically described by way of Examples etc., but the present invention is not limited to these Examples etc. It should be noted that each analysis and evaluation in the Examples etc. was performed by the following methods.

[0100] (1) Ethylene unit content and saponification degree of EVOH

[0101] The dried pellets obtained in each example and comparative example were dissolved in deuterated dimethyl sulfoxide (DMSO-d6) containing tetramethylsilane (TMS) as an internal standard substance and trifluoroacetic acid (TFA) as an additive, and the mixture was measured using a 500 MHz 1H-NMR (manufactured by JEOL Ltd.: "GX-500") was used for measurement at 80°C, and the ethylene unit content and the degree of saponification were determined from the peak intensity ratios of the ethylene unit, the vinyl alcohol unit, and the vinyl ester unit.

[0102] (2) Content of structure (I) and structure (II)

[0103] The dried pellets obtained in each example and comparative example were dissolved in DMSO-d6 containing TMS as an internal standard substance, and the 1 H-NMR (manufactured by JEOL Ltd.: "GX-500") was measured at 45°C, and the contents of structure (I) and structure (II) were determined from the ratio of the peak intensity of ethylene unit, vinyl alcohol unit, and vinyl ester unit to the peak intensity of methyl hydrogen of methoxy group or methylene hydrogen of ethoxy group possessed by structure (I) and structure (II). It should be noted that the peaks of methyl hydrogen of methoxy group possessed by structure (I) and structure (II) were detected at around 3.07 ppm and 3.09 ppm, respectively.

[0104] (3) Metal ion content

[0105] The dried pellets 0.5g obtained by each embodiment and comparative example are put into a pressure vessel made of Teflon (registered trademark), 5mL of concentrated nitric acid is added, and it is left to stand at room temperature for 30 minutes, then, it is covered and heated at 150°C for 10 minutes, then, it is heated at 180°C for 5 minutes, thus wet decomposition is carried out, and thereafter, it is cooled to room temperature. The obtained treatment solution is transferred to a 50mL volumetric flask, constant volume with pure water, and the solution thus obtained is used, and the content of each metal ion is quantified using an ICP emission spectrophotometer. It should be noted that the content of phosphate compounds and boron compounds can also be quantified using the same method.

[0106] (4) Carboxylic acid content

[0107] 10 g of the dried pellets obtained in each example and comparative example and 50 mL of pure water were placed in a 100 mL conical flask with a stopper, and a reflux condenser was installed, and the mixture was heated at 95° C. for 8 hours and then cooled to 20° C. The obtained extract was titrated with a 0.02 mol / L sodium hydroxide aqueous solution using phenolphthalein as an indicator to quantify the carboxylic acid.

[0108] (5) Evaluation of viscosity stability

[0109] The torque change when 60 g of the dried pellets obtained by each example and comparative example were kneaded using Labo Prastomill (two-axis anisotropy) at 100 rpm and 230° C. The ratio (TM / TI) of the average torque value TI during the period from the start of kneading to 1 to 5 minutes later and the maximum torque value TM during the period from the start of kneading to 5 to 20 minutes later was evaluated according to the following criteria A to D (the smaller the number, the better the viscosity stability), as an index of viscosity stability.

[0110] A: less than 1.10

[0111] B: 1.10 or more and less than 1.25

[0112] C: 1.25 or more and less than 1.40

[0113] D: 1.40 and above.

[0114] (6) Evaluation of color fastness under alkaline conditions

[0115] 10 g of the dried pellets obtained by each embodiment and comparative example were heated and melted at 220°C for 6 minutes in a heating and compression pressurizing device to prepare a plurality of disc-shaped test pieces with a thickness of 3 mm. The obtained test piece was immersed in 100 g of a 0.1 mol / L sodium hydroxide aqueous solution, and the lid of the container containing the test piece was closed, and the test piece was left standing at 80°C for 1 week. The test piece was taken out, and its coloration degree was compared visually with that of other test pieces immersed in pure water at 80°C for 1 week, and evaluated according to the following A to D criteria as an index of coloration resistance under alkaline conditions.

[0116] A: Almost indistinguishable by visual inspection

[0117] B: Slight coloring

[0118] C: Slightly colored (light yellow)

[0119] D: Clearly colored (yellow).

[0120] [Synthesis example 1]

[0121] Using a 250 L pressure reaction vessel, polymerization was carried out using the following raw materials and conditions to obtain an ethylene-vinyl acetate copolymer.

[0122] ・Vinyl acetate: 83.0kg

[0123] ・Methanol: 26.6kg

[0124] ・Polymerization initiator: 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (2.5 g / L methanol solution) Initial supply: 362 mL, Continuous supply: 1120 mL / hr

[0125] ・Polymerization temperature: 60℃

[0126] ・Ethylene pressure of polymerization tank: 3.6MPa.

[0127] When the polymerization rate of vinyl acetate reached about 40%, sorbic acid was added, and the polymerization was stopped by cooling. Next, the reaction tank was opened to atmospheric pressure, ethylene was removed from the reaction system, and the reaction solution was supplied to a stripping tower, and methanol vapor was introduced from the bottom of the tower to remove unreacted vinyl acetate from the top of the tower, thereby obtaining a methanol solution of an ethylene-vinyl acetate copolymer having an ethylene unit content of 32 mol%.

[0128] [Synthesis example 2]

[0129] A methanol solution of an ethylene-vinyl acetate copolymer having an ethylene unit content of 24 mol % was obtained by the same operation as in Synthesis Example 1 except that the polymerization conditions were changed as follows.

[0130] ・Vinyl acetate: 102.0kg

[0131] ・Methanol: 17.7kg

[0132] ・Polymerization initiator: 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (2.5 g / L methanol solution) Initial supply: 280 mL, Continuous supply: 850 mL / hr

[0133] ・Ethylene pressure of polymerization tank: 2.9MPa.

[0134] [Synthesis example 3]

[0135] A methanol solution of an ethylene-vinyl acetate copolymer having an ethylene unit content of 27 mol % was obtained by the same operation as in Synthesis Example 1 except that the polymerization conditions were changed as follows.

[0136] ・Vinyl acetate: 85.2kg

[0137] ・Methanol: 32.3kg

[0138] ・Polymerization initiator: 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (2.5 g / L methanol solution) Initial supply: 310 mL, Continuous supply: 950 mL / hr

[0139] ・Ethylene pressure of polymerization tank: 2.9MPa.

[0140] [Synthesis Example 4]

[0141] A methanol solution of an ethylene-vinyl acetate copolymer having an ethylene unit content of 44 mol % was obtained by the same operation as in Synthesis Example 1 except that the polymerization conditions were changed as follows.

[0142] ・Vinyl acetate: 76.7kg

[0143] ・Methanol: 11.0kg

[0144] ・Polymerization initiator: 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (2.5 g / L methanol solution) Initial supply: 510 mL, Continuous supply: 1570 mL / hr

[0145] ・Ethylene pressure of polymerization tank: 5.5MPa.

[0146] [Synthesis example 5]

[0147] A methanol solution of an ethylene-vinyl acetate copolymer having an ethylene unit content of 32 mol % was obtained by the same operation as in Synthesis Example 1 except that the polymerization conditions were changed as follows.

[0148] ・Vinyl acetate: 83.0kg

[0149] ・Methanol: 20.8kg

[0150] ・Polymerization initiator: 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (2.5 g / L methanol solution) Initial supply: 1450 mL, Continuous supply: 4360 mL / hr

[0151] ・Ethylene pressure of polymerization tank: 3.8MPa.

[0152] [Example 1]

[0153] The methanol solution of ethylene-vinyl acetate copolymer obtained by Synthesis Example 1 is put into a saponification reactor, and a 2 mol / L methanol solution of sodium hydroxide (NaOH) is added in such a way that the molar ratio of sodium hydroxide to the vinyl ester component in the copolymer (NaOH / vinyl ester unit) reaches 3, and methanol is further added to adjust the copolymer concentration to 5% by mass. The solution is heated to 60°C and the saponification reaction is carried out for 3 hours while stirring. At this time, in the last hour, the ultrasonic cleaner "US CLEANER USK-2R" is used to irradiate the reaction solution with ultrasound at an output power of 80W and a frequency of 40kHz across the reactor while reacting. Thereafter, acetic acid and water are added to stop the saponification reaction and EVOH is precipitated. The precipitated EVOH is recovered, finely crushed to obtain a water-containing pellet, and then washed with an acetic acid aqueous solution and ion exchange water, and further impregnated with an aqueous solution containing sodium acetate and acetic acid. The aqueous solution was separated from the water-containing pellets and deliquored, and then placed in a hot air dryer, dried at 80°C for 3 hours, and then dried at 110°C for 35 hours to obtain the resin composition of the present invention in the form of dry pellets. The obtained dry pellets were used to perform the above-mentioned analysis and evaluation. It should be noted that in the impregnation treatment, the concentrations of sodium acetate and acetic acid in the aqueous solution were adjusted to obtain a resin composition having sodium and acetic acid contents of 180 ppm and 300 ppm, respectively.

[0154] [Example 2]

[0155] Dry pellets were produced, analyzed and evaluated by the same operations as in Example 1, except that a 2 mol / L methanol solution of sodium hydroxide was added so that the molar ratio of sodium hydroxide to the vinyl ester component in the copolymer (NaOH / vinyl ester unit) was 1.5 and ultrasonic irradiation was performed during the last 15 minutes of the saponification reaction.

[0156] [Examples 3 to 5]

[0157] Dry pellets were produced by the same operation as in Example 1 except that the methanol solution of ethylene-vinyl acetate copolymer obtained in the synthesis example described in Table 1 was used, and were analyzed and evaluated.

[0158] [Example 6]

[0159] Dry pellets were produced, analyzed and evaluated in the same manner as in Example 1 except that potassium acetate was used instead of sodium acetate and the concentrations of the components in the aqueous solution for immersion treatment were adjusted so that the contents of potassium and acetic acid were 300 ppm and 300 ppm, respectively.

[0160] [Example 7]

[0161] The methanol solution of ethylene-vinyl acetate copolymer obtained by synthesis example 1 is put into a polytetrafluoroethylene resin reactor, and 2 mol / L methanol solution of sodium hydroxide is added in a manner that the molar ratio of sodium hydroxide to the vinyl ester component in the copolymer (NaOH / vinyl ester unit) reaches 3, and methanol is further added to adjust the copolymer concentration to 5%. The obtained solution is placed in a microwave irradiation device (Anton Paar company system, Multiwave3000 type) and sealed, and stirring is started. The output power is set to 800W, and the temperature is raised to 60°C, and then kept for 2 hours. Here, the frequency of the microwave irradiated to the reaction solution is 2450MHz (2.45GHz). Thereafter, the reactor is taken out from the microwave irradiation device, and after natural cooling at room temperature, acetic acid and water are added to stop the saponification reaction, and EVOH is precipitated. The precipitated EVOH is recovered, and after finely pulverized to obtain a water-containing pellet, it is cleaned with an acetic acid aqueous solution and ion exchange water, and further impregnated with an aqueous solution containing sodium acetate and acetic acid. The aqueous solution was separated from the water-containing pellets and deliquored, and then placed in a hot air dryer, dried at 80°C for 3 hours, and then dried at 110°C for 35 hours to obtain the resin composition of the present invention in the form of dry pellets. The obtained dry pellets were used to perform the above-mentioned analysis and evaluation. It should be noted that in the impregnation treatment, the concentrations of sodium acetate and acetic acid in the aqueous solution were adjusted to obtain a resin composition having sodium and acetic acid contents of 180 ppm and 300 ppm, respectively.

[0162] [Comparative Example 1]

[0163] Dry pellets were produced, analyzed and evaluated by the same operation as in Example 1 except that a 2 mol / L methanol solution of sodium hydroxide was added so that the molar ratio of sodium hydroxide to the vinyl ester component in the copolymer (NaOH / vinyl ester unit) was 0.8 and ultrasonic irradiation was not performed.

[0164] [Comparative Example 2]

[0165] Except for using the methanol solution of the ethylene-vinyl acetate copolymer obtained in Synthesis Example 5, the same operation as in Example 1 was carried out to produce dry pellets, and the analysis and evaluation were carried out.

[0166] [Comparative Example 3]

[0167] Except having used the methanol solution of the ethylene-vinyl acetate copolymer obtained in Synthesis Example 5, the same operation as in Comparative Example 1 was carried out to produce dry pellets, and the analysis and evaluation were carried out.

[0168] The contents of structures (I) and (II) in each resin composition obtained in the embodiments and comparative examples, their ratios and evaluation results are shown in Table 1. The total content of structure (I) and structure (II) is 0.002 to 0.020 mol %, and the viscosity stability of the resin composition of the present invention satisfying the above formula (1) is excellent at the beginning of melting. In addition, the appearance characteristics of these resin compositions after melt forming are also excellent. On the other hand, the viscosity of each resin composition of the comparative example at the beginning of melting changes greatly, and the melt forming process is unstable.

[0169]

Claims

1. Ethylene-vinyl alcohol copolymer, wherein The ethylene unit content is 15 to 60 mol%, and the saponification degree is 85 mol% or more. The copolymer comprises a molecule having the following structure (I) at the terminal and a molecule having the following structure (II) at the terminal, wherein the total content of the structure (I) and the structure (II) is 0.002 to 0.020 mol% relative to all monomer units, and The molar ratio R [I / (I+II)] of structure (I) to the sum of structure (I) and structure (II) satisfies the following formula (1): [Chemistry 1] In formula (I), Y is a hydrogen atom or a methyl group; [Chemistry 2] In formula (II), Z is a hydrogen atom or a methyl group; 0.9 <R+Et / 100 (1) In formula (1), Et is the ethylene unit content, expressed in mol%.

2. A resin composition comprising the ethylene-vinyl alcohol copolymer according to claim 1 and 100 to 400 ppm of metal ions. 3 . The resin composition according to claim 2 , comprising 50 to 400 ppm of the carboxylic acid. A shaped body comprising the ethylene-vinyl alcohol copolymer according to claim 1.

5. A molded body comprising the resin composition according to claim 2 or 3.

6. The method for producing an ethylene-vinyl alcohol copolymer according to claim 1, comprising the following steps: a copolymerization step of copolymerizing ethylene and vinyl ester in a solution using an alkoxy-containing azonitrile compound as a polymerization initiator to obtain an ethylene-vinyl ester copolymer solution; and a saponification step of saponifying the ethylene-vinyl ester copolymer in the solution in the presence of an alkali catalyst to obtain an ethylene-vinyl alcohol copolymer. In the saponification step, 1.2 mol or more of a base catalyst is used relative to 1 mol of the vinyl ester component contained in the ethylene-vinyl ester copolymer, and the solution is irradiated with ultrasonic waves or microwaves.

Citation Information

Patent Citations

  • Antioxidant ethylene / vinyl alcohol polymer composition

    JP1992227744A

  • Production of vinyl acetate-based polymer, production of saponified vinyl acetate-based polymer and resin composition

    JP1997071620A

  • Saponified ethylene-vinyl acetate copolymer composition and multilayer structure prepared therefrom

    JP1999060874A

  • Resin composition containing ethylene-vinyl alcohol copolymer

    WO2013146961A1

  • Multilayered structure, laminate and methods for producing same

    CN103097129A

Cited By

  • Ethylene-vinyl alcohol copolymer composition as well as preparation method and application thereof

    CN121652498A